Kinerja Keuangan Sebelum dan Sesudah Kebijakan Amnesti Pajak: Suatu Analisis Komparatif - Churniawati, Ninik (Universitas Muhammadiyah Yogyakarta, 2019)
The purpose of this research is to know the difference in financial performance before and after the Tax Amnesty policies. The population in this research is the company sub-sectors automotive and its components. The data used are secondary data (the published financial reports) through the website www.idx.co.id. Hypothesis testing is done by testing paired sample t-test. The results showed that there is a difference but not significant financial performance Current ratio (CR), Return On Equity (ROE), DER, EPS and AT both before and after the tax amnesty policy. From table test paired sample t-tests can be noted that CR has difference before and after the tax amnesty are the highest, because the value of the least significance, namely of 0.196, and financial performance AT least has the distinction because of the value greatest significance, namely of 0.893